2009
DOI: 10.1016/j.drugalcdep.2008.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Cost analysis of clinic and office-based treatment of opioid dependence: Results with methadone and buprenorphine in clinically stable patients

Abstract: The cost of providing and receiving treatment for opioid dependence can determine its adoption. To compare the cost of clinic-based methadone (MC, n=23), office-based methadone (MO, n=21), and office-based buprenorphine (BO, n=34) we performed an analysis of treatment and patient costs over 6 months of maintenance in patients who had previously been stabilized for at least one year. We performed statistical comparisons using ANOVA and chi-square tests and performed a sensitivity analysis varying cost estimates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 32 publications
1
46
0
Order By: Relevance
“…Buprenorphine/naloxone treatment may be particularly attractive because it provides greater privacy, is less stigmatized than receiving methadone treatment, and is similar to treatment for other chronic medical problems. However, in spite of its appeal and efficacy, providers caring for individuals with a history of incarceration should be aware of potential financial barriers to paying for buprenorphine/naloxone, 40,41 as well as structural ones to continuing buprenorphine/naloxone in correctional facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Buprenorphine/naloxone treatment may be particularly attractive because it provides greater privacy, is less stigmatized than receiving methadone treatment, and is similar to treatment for other chronic medical problems. However, in spite of its appeal and efficacy, providers caring for individuals with a history of incarceration should be aware of potential financial barriers to paying for buprenorphine/naloxone, 40,41 as well as structural ones to continuing buprenorphine/naloxone in correctional facilities.…”
Section: Discussionmentioning
confidence: 99%
“…31 Following methods used in that cost study, we applied local labor and fringe benefit rates for physicians and nurses to the visit durations to determine visit costs, adding an additional 22% of the cost to account for time lost due to missed visits and a 46% overhead rate. 31,32 A similar approach was used to calculate average monthly utilization and costs for urine toxicology tests from the study data, and we also assumed liver enzyme tests (alanine aminotransferase, aspartate aminotransferase) occurred every 3 months while in treatment. 25 Patient costs, including visit time, travel time, and monthly transportation costs, were derived from the previous cost study.…”
Section: Costsmentioning
confidence: 99%
“…25 Patient costs, including visit time, travel time, and monthly transportation costs, were derived from the previous cost study. 31 Time costs were calculated by multiplying the duration of the visit and travel by the state minimum wage of $8.25 per hour, 33 as more than half of the cohort reported not having full-time employment. 25 …”
Section: Costsmentioning
confidence: 99%
“…29 One recent study found the cost of providing 1 month of treatment per patient was $147 in methadone clinic treatments, $220 in methadone office treatments, and $336 buprenorphine office treatments (P < 0.001). 30 Mean monthly medication cost was $93, $86, and $257, respectively (P < 0.001). The cost to patients was $92, $63, and $38, respectively (P = 0.102), demonstrating that while the overall cost of buprenorphine is higher, the cost to the patient for buprenorphine therapy is lower.…”
mentioning
confidence: 99%
“…The cost to patients was $92, $63, and $38, respectively (P = 0.102), demonstrating that while the overall cost of buprenorphine is higher, the cost to the patient for buprenorphine therapy is lower. 30 Another analysis of 259 published articles of economic evaluations of treating opiate dependence found that most studies used narrow treatment perspectives and surrogate outcome measures, concluding that the quantity and quality of economic evaluations are limited, evidence on cost-effectiveness of psychosocially-assisted pharmacotherapy is virtually nonexistent, and that most economic evaluations of treatment options are limited in terms of the range of costs and benefits considered. 31 respectively.…”
mentioning
confidence: 99%